The role of the Jordanian banking system in alleviating the repercussions of the global financial crisis on the Jordanian economy (field study) - Ahmed Youssef Dodin (Iraqi Journal for Administrative Sciences, 2025)
This study aims to identify the impact of the global financial crisis on the Jordanian economy, the role of the Jordanian banking system to ease their repercussions on the economy, from the perspective of employees in commercial banks in Jordan. The study population consists of employees in the departments of banking facilities and branch managers in commercial banks of Jordan, who estimated about (253) employees, were selected by stratified random sample (44.2%) of the study and who numbered (112) employees. For the purpose of achieving the objectives of this research; a questionnaires was designed, consisting of (25) paragraph measure the perceptions of employees in the banking sector about the role of the Jordanian banking system to ease the global financial crisis on the Jordanian economy. Theoretical framework was developed for the study by reviewing the literature of research in the field of the global financial crisis, in addition to previous studies on this subject and after collecting the initial data for the study of the questionnaires, and statistical analysis, this research is to find a set of findings and recommendations. One of the main results of the Jordanian banks resorted to the activation of preventive control, and activates the credit risk management, and reduces operational expenses, to counter the global crisis and its repercussions, and increased non-debt ratios have The most important recommendations: continuation of the Central Bank of Jordan in the effective and significant role in banking supervision on banks, and to emphasize the application of corporate governance. As well as the continuation of commercial banks to take responsibility to stimulate and activate the direction and development of the Jordanian economy, as well as to assume its social responsibility the direction of its employees, and the direction of the Jordanian society within which they operate. The Key words: The Global Financial Crisis, The Jordanian Banking System